2022
DOI: 10.3390/f13040589
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Radial Variation in Basic Density of Pendulate Oak: Comparing Increment Core Samples with the IML Power Drill

Abstract: To determine the appropriate final use of wood from a particular tree species, it is first necessary to know its properties. Methods that use wood samples taken directly from the trunk of a growing or felled tree are very time-consuming and require a great deal of manual work. Non-destructive methods may be more effective and much faster, thanks to the use of advanced technologies. The resistance drilling can be used to determine the variation in wood density along the radius of the stem. The main aim of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Tomczak et al measured the radial basic density of nine oak trees with an increment corer and IML (Instrumenta Mechanik Labor, Australia) power drill. The results indicated that the determination coefficient of the linear model between the average drill resistance and wood density was 0.396 [40]. Close relationships existed in the regression model between the amplitude of the drilling resistance and wood density in previous research on trees in a breeding program (R 2 > 0.60) [41], lumber and the linear regression model for agarwood (R 2 = 0.25) [42].…”
Section: Discussionmentioning
confidence: 68%
“…Tomczak et al measured the radial basic density of nine oak trees with an increment corer and IML (Instrumenta Mechanik Labor, Australia) power drill. The results indicated that the determination coefficient of the linear model between the average drill resistance and wood density was 0.396 [40]. Close relationships existed in the regression model between the amplitude of the drilling resistance and wood density in previous research on trees in a breeding program (R 2 > 0.60) [41], lumber and the linear regression model for agarwood (R 2 = 0.25) [42].…”
Section: Discussionmentioning
confidence: 68%
“…Rinn et al found that the feed resistance of the drill needle does not contain additional important information. Therefore, most scholars have studied the correlation between drill needle rotation resistance and wood density [37][38][39][40]. In order to study the correlation between the feed resistance of drilling needles and wood density, the paper designed a micro drilling instrument that can simultaneously measure the rotation resistance and feed resistance of drilling needles.…”
Section: Discussionmentioning
confidence: 99%
“…There are an increasing number of studies in the scientific literature utilising the drilling resistance for wood density assessment, predominantly in tree breeding [12][13][14]. Studies have also used the approach to explore longitudinal and radial variation in wood properties within the tree [15][16][17] and silvicultural and environment effects on wood properties [15,18,19]. Work in both softwoods and hardwoods has demonstrated that drilling resistance data correlates strongly at the individual sample level with basic density [8,16,20,21].…”
Section: Introductionmentioning
confidence: 99%